KEMAMPUAN FITOREMEDIASI TYPHA LATIFOLIA DALAM MENURUNKAN KADAR LOGAM KADMIUM (CD) TANAH YANG TERCEMAR LUMPUR LAPINDO DI PORONG SIDOARJO - FITRA, ALFAN (LenteraBio: Berkala Ilmiah Biologi, 2013)
Lapindo mud Cd contaminated soil is above the threshold limit of 3.0 mg/kg. One way to control Cd in the soil is the use of plant T. latifolia to reduce the levels of heavy metals in soil and water. The purpose of this study was to determine the effect of the number of T. latifolia and detention time on decreased Cd contain in Lapindo mud contaminated soil as amedia, and Cd contain in the plant root T. latifolia and the relation between Cd contain in the plant root of T. latifolia with decreased contain of Cd in lapindo mud contaminated soil. The method used was experimental factorial randomized block design with two factors T. latifolia, the number of plants T. latifolia (without plants, 1 plants, and 2 plants) and detention time (7 days and 14 days) using 4 replication. Parameters of this study were decreased levels of Cd in the media and Cd contain in the roots of T. latifolia. Data were analyzed using quantitative descriptive statistics. The results showed that on plant number and detention time affected decreased levels of Cd in the media and Cd contain in the root of T. latifolia. There was also a correlation between elevated Cd contain in the roots of T. latifolia and decreased Cd contain in the media. Highest contain of Cd in the roots and decreased contain of Cd in the media was found when the two plants was combinated by detention time of plants with a value of 15.04 mg/kg (1.504 %) and 17.03 mg/kg (59,05 %) respectively. Keywords : Lapindo mud contaminated soil; Typha latifolia; cadmiun (Cd)